2015
DOI: 10.1002/dta.1830
|View full text |Cite
|
Sign up to set email alerts
|

Hair analysis for Δ9‐tetrahydrocannabinolic acid A (THCA‐A) and Δ9‐tetrahydrocannabinol (THC) after handling cannabis plant material

Abstract: A previous study has shown that Δ(9) -tetrahydrocannabinolic acid A (THCA-A), the non-psychoactive precursor of Δ(9) -tetrahydrocannabinol (THC) in the cannabis plant does not get incorporated in relevant amounts into the hair through the bloodstream after repeated oral intake. However, THCA-A can be measured in forensic hair samples in concentrations often exceeding the detected THC concentrations. To investigate whether the handling of cannabis plant material prior to consumption is a contributing factor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…THCAA concentrations were monitored in plasma and whole blood [24], blood serum and urine [25] and oral fluid [26, 27]. THCAA also was demonstrated in hair after cannabis consumption, passive exposure and external contamination [28, 29]. The plant constituent THCV was recently administered in a controlled study investigating if THCV inhibits THC effects [30], as it was suggested that THCV is a receptor neutral antagonist [31].…”
Section: Discussionmentioning
confidence: 99%
“…THCAA concentrations were monitored in plasma and whole blood [24], blood serum and urine [25] and oral fluid [26, 27]. THCAA also was demonstrated in hair after cannabis consumption, passive exposure and external contamination [28, 29]. The plant constituent THCV was recently administered in a controlled study investigating if THCV inhibits THC effects [30], as it was suggested that THCV is a receptor neutral antagonist [31].…”
Section: Discussionmentioning
confidence: 99%
“…In forensic cases, hair samples are often used as evidence for drug use, as trace amounts of certain compounds can be detected in hair. THC and THCA‐A are not suitable markers for cannabis intake due to the potential for external contamination, such as in the adsorption of second‐hand smoke by hair . Therefore, a primary metabolite of THC, 11‐nor‐9‐carboxy‐THC (THC‐COOH), is typically used as a marker to confirm the intake of cannabis (Supplementary Fig.…”
mentioning
confidence: 99%
“…THC and THCA-A are not suitable markers for cannabis intake due to the potential for external contamination, such as in the adsorption of second-hand smoke by hair . [1,2] Therefore, a primary metabolite of THC, 11-nor-9-carboxy-THC (THC-COOH), is typically used as a marker to confirm the intake of cannabis ( Supplementary Fig. S1, see Supporting Information).…”
mentioning
confidence: 99%
“…External hair contamination of THCA‐A has been reported, caused primarily by handling Cannabis sativa plant material and side stream smoke . Diffusion and incorporation of the cannabinoid into the hair matrix can therefore occur, which cannot be completely removed, even by extensive washing/decontamination steps.…”
Section: Resultsmentioning
confidence: 99%